Siberian Roe Deer (Capreolus pygargus Pallas, 1771) in Ukraine: Analysis of the Mitochondrial and Nuclear DNA - Danilkin, A.; Plakhina, D.; Zvychaynaya, E.; Domnich, A.; Kholodovа, M.; Sorokin, P.; Volokh, Anatolii; Волох, Анатолій Михайлович; Волох, Анатолий Михайлович (My University, 2017)
A molecular-genetic analysis of the nucleotide sequences of the cytochrome b gene (1140 base pairs) of the mitochondrial DNA and 17 microsatellite loci of eight samples of roe deer from the Samara forest of Dnipropetrovsk oblast (Ukraine) was carried out. For comparison, 212 corresponding mtDNA sequences of the Siberian and European roe deer and data on the variability of microsatellite markers in 49 representatives of these species were included in the study. It was noted that all the analyzed mitochondrial sequences of individuals from the Samara forest are characteristic of the Siberian roe Capreolus pygargus Pallas, 1771. Four haplotypes were described, all of which belonged to the haplogroup typical for the western part of the range of C. pygargus. A fragment analysis of the microsatellite loci of nuclear DNA confirmed the identification of the investigated group with the Siberian species.